THE POTENTIAL OF LIQUEFACTION DISASTERS BASED ON THE GEOLOGICAL, CPT, AND BOREHOLE DATA AT SOUTHERN BALI ISLAND - Sinarta, I Nengah; Basoka, I Wayan Ariyana (Journal of Applied Engineering Science, 2019)
Following the incident in Petobo, Palu, liquefaction becomes a very important object for in-depth study. That incident caused enormous loss of life and severe damage to the infrastructure. Soil investigation by the CPT (cone penetration test) method has been carried out at Jalan Taman Pancing, Pemogan village, Southern Bali Island area to determine the composition of soil layers, the bearing capacity of the soil, and the thickness of each layer of soil. Analysis of liquefaction potential was carried out using geological interpretation the CPT data based on deterministic analysis using Stress Based Method, using the 2017 Seismic Hazard Map of Indonesia for Bali island where the earthquake acceleration reaches 0.4-0.5g, meaning that Bali is highly vulnerable to earthquake, with the largest earthquake magnitude is the Mount Agung eruption measuring 6 on the Richter scale, which rocked Bali on May 18, 1963. The soil investigation shows that the layers of soil consist of sandy silt and silty clay at a depth between 0.5 - 12.0 m and the local water table. Geological conditions with the Qa code alluvium deposits from ancient Buyan-Beratan Mountains. Deterministic analysis based on the CPT data and local geological conditions indicates that the thickness of the soil varies between 1.5 m and 9.5 m, while the safety factor of the liquefaction potential is in the critical conditions between 1.25 - 1.00.